A simple damage detection indicator using operational deflection shapes. (May 2016) - Sampaio, R.P.C.; Maia, N.M.M.; Almeida, R.A.B.; Urgueira, A.P.V.
Abstract: Catastrophic structural failure of aircrafts, bridges, buildings and other structures in modern societies has always been of primary concern because of the loss of human lifes and of negative economic impact. The aging of the structures, the growing dependency on their role in our networks of transportation, energy and comunications, the smaller construction tolerances, the bigger power demanded and the media and society awardness to catastrophic events are sufficient motivations for the growing field of structural health monitoring, which aims at assessing the actual condition of a structure and to identify incipient damage. Damage identification can be considered as a two step process, the detection and the diagnosis. The former, and fundamental step, is the confirmation of an efective damage existence. When the response is affirmative, the latter step begins with the diagnosis, and then the questions are: where?, how much?, what type?, when will it fail? In this paper the authors propose a simple method to detect and relatively quantify structural damage by using measured vibrations data, specifically the operational deflections shapes. Numerical simulations and experimental tests are presented to validate the proposed method. Highlights: New detection indicator, based on ODSs. Very simple. Sensitive Indicator.